Modification of MTT Assay for Precision and Repeatability and Its Mechanistic Implication - Wang, Xu-Dong; Deng, Rui-Cheng; Liu, Yao; Li, Biao; Huang, Shen; Ouyang, Hui; Xiao*, Zhu-Ping (Asian Journal of Chemistry, 2014)
The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay is an attractive method for antibiotics screening. However, a severe deviation will occur when a strong acidic sodium dodecyl sulfate is used as a lysis buffer in MTT assay and no literatures so far reported the possible reasons. Based on the results of MTT assay and the UV absorption-pH curves of MTT formazan, we putatively attributed this deviation to the presence of the cationic MTT formazan in strong acidic media, which results in a complete disappearance of the peak at 575 nm. Our data suggested that the pH of sodium dodecyl sulfate lysis buffer should be controlled at about 3.5 for more accurate and repeatable results. In addition, the microbial concentration in antibacterial activity test can be directly obtained from the standard curves of microbial concentration against optical density at 600 nm. In comparison with the traditional processes for MTT assay, the above mentioned improvements significantly increase the accuracy and repeatability of this attractive method.